Analisis Hukum Islam dan Hukum Positif terhadap Pemenuhan Hak-Hak Istri dan Anak Pasca Percerian dalam Perkara Cerai Gugat: Analisis Putusan Pengadilan Agama Kalianda Nomor: 407/Pdt.G/2025/Pa.Kla - Iqbal Syarief Saputra; Yusuf Baihaqi; Syeh Sarip Hadaiyatullah (Jurnal Hukum Lex Generalis, 2026)
This study analyzes the Decision of the Kalianda Religious Court Number 407/Pdt.G/2025/PA.Kla concerning the fulfillment of the rights of wives and children after divorce in a contested divorce case. The legal issue examined in this study is how legal protection for child custody (hadanah), child support, iddah maintenance and mut’ah is provided when the divorce is caused by neglect of financial support and domestic conflict. This decision was selected because it demonstrates the use of the judge’s ex officio authority in determining the rights of women and children, even though the case was filed as a contested divorce. This research employs a normative-juridical method using statutory and court decision approaches. The results show that the judges considered not only formal juridical aspects, but also sociological aspects and the best interests of the child. The decision reflects the integration of Islamic law and positive law in providing fair legal protection for women and children after divorce.